KNOWLEDGE AND ATTITUDE OF UNDERGRADUATE DENTAL STUDENTS TOWARDS RESEARCH - Habib, Syed Rashid; AlOtaibi, Saad Saud; Abdullatif, Fahad Abdulrahman; AlAhmad, Ibrahim Mohammed (Journal of Ayub Medical College Abbottabad, 2018)
Background: Scientific research is an important part of healthcare curricula and a vital exercise to help develop clinician’s research skills. The aim of this study was to evaluate quantitatively the knowledge and attitude of undergraduate dental students towards scientific research. In addition, the study explored the reasons for lack of interest in research by the dental students. Methods: This cross-sectional study was conducted among students of three dental schools in Riyadh. The required information was collected through a self-designed, pretested and validated questionnaire used for investigating the students’ knowledge, attitudes and reasons for lack of interest if any in research. Descriptive, chi-square and t-tests were used for statistical analysis of the responses considering a p-value of <0.05 as the cut-off level for significance. Results: Out of 701 completed questionnaires (Response Rate=77.88%), 360 (51.4%) and 341 (48.6%) were for males and female students respectively. Subjects, stratified according to year of study, included students of first year=144 (20.5%); second year=151 (21.5%); third year=132 (18.8%); fourth year=145 (20.7%) and fifth year=129 (18.4%). The mean and standard of the knowledge score was 3.36+1.76 and attitude score was 3.87±2. Students’ knowledge and attitude scores tended to increase as the study year went higher. Conclusion: A moderate level of knowledge about research was found among dental students. However, attitude of the dental students towards research was positive. Improvements were seen in the knowledge and attitude of students over the study years. Curriculum overload, exposure, literature search, knowledge and finding a topic or mentor in the school seemed to be the barriers in pursuing research. Keywords: Dental Student; Research; Attitude; Barrier; Research Knowledge